CONFLICT MANAGEMENT BETWEEN TANJUNG PAUH MUDIK VILLAGE AND KUMUN VILLAGE IN KERINCI DISTRICT - Nosy Mutia Angraini (LPPM Ekasakti University, 2022)
This article aims to describe the conflict management between Tanjung Pauh Mudik and Kumun and conflict management that can be applied in other regions in Indonesia if there is a similar thing identified from the factors that cause conflict, the impact of conflict and efforts to resolve and manage it . The study used a qualitative approach with descriptive methods. The selection of research informants used purposive sampling (purposive sampling). Data is collected through observation, document analysis, and interviews. While the data analysis techniques are data collection, data reduction, data presentation and conclusion drawing. The results showed that conflict management was carried out, namely making a letter of peace agreement through dialogue with both parties, enacting customary rules that prohibit teenagers from wandering in the village to the neighboring village boundary past 11pm, paying compensation for those who suffered losses, socializing from each village government to the younger generation and parents, activating various activities involving youth in each village, and holding joint iftar between the youth of both parties. This management effort is carried out based on the factors that cause conflict (hatred, impatience, distrust, intolerance, inability to understand each other, inability to forgive one another, and youth mischief) and the effects of conflict (economic, physical, socio-cultural losses) , and psychic).